An Empirical Test of the Reder Hypothesis - Johannes Ludsteck; Harald Haupt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
A firm that faces insufficient supply of labor can either increase the wage offer to attract more applicants, or reduce the hiring standard to enlarge the pool of potential employees, or do both. This simultaneous adjustment of wages and hiring standards in response to changes in market conditions has been emphasized in a classical contribution by Reder and leads to the effect that wage reactions to employment changes can be expected to be more pronounced for low wage workers than for high wage workers. This is the `Reder Hypothesis'. The present contribution sets out to test this hypothesis using German employment register data and a censored panel quantile regression approach. Our findings support the Reder Hypothesis, suggesting that market clearing in labor markets is achieved by a combination of wage adjustments and changes in hiring standards.
urn:nbn:de:bvb:19-epub-1397-5
Keywords: J31; J41; C24; 330; standards; overqualification; wage structure; panel quantile regression; censoring; Arbeitsnachfrage; Lohnstruktur; Kündigung; Schätztheorie; Theorie